2020
DOI: 10.3389/fpsyg.2020.02196
|View full text |Cite
|
Sign up to set email alerts
|

“Let’s Get Out of Here!”: Cognitive Motivation and Maximizing Help Teams Solving an Escape Room

Abstract: Contemporary teams often face complex problem-solving tasks. We theorized that two individual differences previously neglected in team research (cognitive motivation and maximizing) would be helpful for teams facing such situations. We tested this assertion on 81 teams participating in an escape-room simulation in which teams were locked into a pre-arranged room and had to solve various complex problems to escape the room as quickly as possible. The findings show that the average of the team members’ cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Whilst most of the participants were moderately to very motivated to play the DER, some were not keen on this activity. The statistical analyses performed do not allow us to establish a causal relationship between the students' prior level of motivation and their learning experience, but cognitive motivation has been linked to performance whilst playing an escape room before ( Gómez-Urquiza et al, 2019 ; Schei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst most of the participants were moderately to very motivated to play the DER, some were not keen on this activity. The statistical analyses performed do not allow us to establish a causal relationship between the students' prior level of motivation and their learning experience, but cognitive motivation has been linked to performance whilst playing an escape room before ( Gómez-Urquiza et al, 2019 ; Schei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, a team of all maximizers may spend too long exploring every possible innovation at the expense of not actually moving forward on any specific product. In one study involving an escape room game where participants must solve puzzles in a certain amount of time to win, or escape the room, teams with higher mean maximization scores only performed better when they cooperated (Schei et al, 2020). Interestingly, teams with just one maximizer also benefited by generating more alternatives through cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Maximization has long had a negative reputation, with many studies showing negative relationships between maximization and well-being (e.g., Schwartz et al, 2002;Purvis et al, 2011;Oishi et al, 2014;Cheek and Schwartz, 2016). It is only recently that some scholars have raised skepticism regarding the negative associations and turned their attention to potential positive aspects of maximization (e.g., Kokkoris, 2016;Misuraca et al, 2016;Zhu et al, 2017;Peng et al, 2018;Schei et al, 2020;Brannon, 2021;Ma et al, 2021;Li et al, 2023). Li et al (2023) found that students with a strong maximizing tendency have better adjustment skills after their first year of studies and attain higher GPAs upon completing their bachelor's degrees.…”
Section: Positive Aspects Of Maximizing Tendency In the Covid-19 Pand...mentioning
confidence: 99%
“…But do maximizing tendencies always play a negative role in one's well-being? In recent years, some researchers have begun to explore novel and positive aspects of maximizing tendencies and their positive effects on well-being (e.g., Kokkoris, 2016;Misuraca et al, 2016;Zhu et al, 2017;Peng et al, 2018;Schei et al, 2020;Brannon, 2021;Ma et al, 2021;Li et al, 2023). They highlighted maximizers' greater level of future-oriented thinking (Misuraca et al, 2016;Zhu et al, 2017) and intrinsic and achievement motivation (Lai, 2011;Peng et al, 2018), qualities which have been regarded as valuable predictors of adaptability (e.g., Griffin and Hesketh, 2005;Bell and Kozlowski, 2008;Stokes et al, 2010;Anagnostopoulos and Griva, 2012).…”
Section: Introductionmentioning
confidence: 99%